ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF NICHE COOPERATION DEVELOPMENT - CHATA, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the organizational and economic foundations for the development of niche cooperation as an innovative form of interaction among economic entities. It defines the essence, key characteristics, and distinctive features of niche cooperation in the context of modern economic transformations. The research emphasizes the strategic importance of cooperation in enhancing the competitiveness of enterprises and communities, fostering sustainable development, and improving adaptability to external challenges such as globalization, digitalization, and market volatility. Particular attention is devoted to the analysis of organizational models and economic instruments that determine the effectiveness of cooperative activities within different sectors of the economy.The article identifies and systematizes the main factors influencing the evolution of niche cooperation, including institutional support, resource availability, and innovation potential. It examines the mechanisms of partnership formation among small and medium-sized enterprises, agricultural producers, and territorial communities, focusing on the creation of added value chains and local economic networks..Furthermore, the research outlines the barriers that limit the expansion of niche cooperation, including insufficient regulatory frameworks, low levels of trust, and limited access to financing. To address these issues, the article proposes the implementation of cluster models and smart specialization principles that facilitate the development of innovative ecosystems. These approaches contribute to strengthening the resilience and competitiveness of communities while promoting inclusive economic growth.The findings of the study have both theoretical and practical significance, offering recommendations for policymakers, entrepreneurs, and local authorities on optimizing organizational and economic mechanisms of niche cooperation. The paper concludes that the integration of digital innovations and financial tools into cooperative systems forms a foundation for sustainable, adaptive, and competitive development within the modern market economy.
Keywords: niche cooperation; instruments; market economy; organizational and economic mechanism; innovations; community competitiveness; clusters